Dysregulated expression of STAT1, miR‐150, and miR‐223 in peripheral blood mononuclear cells of coronary artery disease patients with significant or insignificant stenosis. Issue 12 (18th July 2019) - Saadatian, Zahra; Nariman‐Saleh‐Fam, Ziba; Bastami, Milad; Mansoori, Yasser; Khaheshi, Isa; Parsa, Saeed Alipour; Daraei, Abdolreza; Vahed, Sepideh Zununi; Yousefi, Bahman; Kafil, Hossein Samadi; Eyvazi, Shirin; Ghaderian, Sayyed Mohammad Hossein; et al.
Abstract: Coronary artery disease (CAD) is a multicellular disease characterized by chronic inflammation. Peripheral blood‐mononuclear cells (PBMCs), as a critical component of immune system, actively cross‐talk with pathophysiological conditions induced by endothelial cell injury, reflecting in perturbed PBMC expression. STAT1 is believed to be relevant to CAD pathogenesis through regulating key inflammatory processes and modulating STAT1 expression play key roles in fine‐tuning CAD‐related inflammatory processes . This study evaluated PBMC expressions of STAT1, and its regulators (miR‐150 and miR‐223) in a cohort including 72 patients with CAD with significant ( ≥ 50%) stenosis, 30 patients with insignificant ( < 50%) coronary stenosis (ICAD), and 74 healthy controls, and assessed potential of PBMC expressions to discriminate between patients and controls. We designed quantitative real‐time polymerase chain reaction (RT‐qPCR) assays and identified stable reference genes for normalizing PBMC quantities of miR‐150, miR‐223, and STAT1 applying geNorm algorithm to six small RNAs and five mRNAs. There was no significant difference between CAD and ICAD patients regarding STAT1 expression. However, both groups of patients had higher levels of STAT1 than healthy controls. miR‐150 and miR‐223 were differently expressed across three groups of subjects and were downregulated in patients compared with healthy controls, with the lowest expression levels being observed in patients with ICAD. ROC curves suggested that PBMC expressions may separate between different groups of study subjects. PBMC expressions also discriminated different clinical manifestations of CAD from ICADs or healthy controls. In conclusion, the present study reported PBMC dysregulations of STAT1, miR‐150, and miR‐223, in patients with significant or insignificant coronary stenosis and suggested that these changes may have diagnostic implications. Abstract : Dysregulated PBMC expression of STAT1, miR‐150, and miR‐223, in patients with significant or insignificant coronary stenosis may have diagnostic implications.